Mental illness attitudes in medical education: assessing the stigma in medical students - Márquez Cervantes, Ernesto; Romero Guerra, Daniela Haydé; Costilla Esquivel, Antonio (Instituto Nacional de Psiquiatría Ramón de la Fuente Muñiz, 2023)
Factors affecting the quality of physician care include a shortage of trained staff, stigma, and discrimination. Objective. The objective was to compare the intensity of stigmatization before and after a Psychiatry course, as measured by the scale of clinicians’ attitudes towards mental illness, a version for medical students (MICA-2) designed to identify stigmatic attitudes towards mental disorders. Method. The fifth-year Medicine students enrolled in the Psychiatry course answered anonymously using the MICA-2 test at the start and the end of their course. Additionally, we asked the students to answer a question about their interest in learning more about mental illness. Results. Three hundred and thirty students were invited; 300 agreed to participate in the first application of the scales, and 291 in the follow-up. The average age was 22 ± 2 years,with a range of 20-30 years, and there was a similar gender distribution in both applications. In the initial application, the average score of the MICA-2 was 41.34 (SD = 7.86, 95% CI = [40.43, 42.25]). The follow-up application’s mean was 37.10 (SD = 8.15, 95% CI = [36.30, 38.15]). Also, there was a decrease in interest in learning more about mental illness. Discussion and conclusion. A reduction in the average scores of the MICA-2 was observed after a Psychiatry course, suggesting that attitudes toward mental disorders improved. A Psychiatry clerkship with close supervision modified the attitudes of medical students toward mental disorders. However, it did not increase their interest in learning more about mental illness.